PERAN BELANJA SUBSIDI TRANSPORTASI TERHADAP MOBILITAS PENDUDUK PADA TRANSJAKARTA - Indah Yuli Kustianah; Helena Maniku; Shafa Kamilah Maryza; Najwa Nur Kamila; Andini Khoirunnissa; Dudi Duta Akbar (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study analyzes the role of transportation subsidy expenditure in supporting population mobility through TransJakarta services from the perspective of governmental accounting. Using a descriptive approach through literature review and documentation study, this research examines the relationship between subsidies as fiscal input, service improvement as output, and mobility as policy outcome. Data were obtained from the 2024 Regional Government Financial Report of DKI Jakarta Province, Statistics Indonesia publications, and relevant studies on transportation subsidies and urban mobility. The findings show that transportation subsidies are associated with improved mobility indicators, reflected in the increase in TransJakarta passengers from approximately 285 million in 2023 to 413 million in 2025. Service improvements also supported wider mobility access. However, these improvements cannot be attributed solely to subsidies without further causal testing. The decline in subsidy per passenger indicates potential efficiency improvement in budget utilization.